2016
DOI: 10.1142/s2010139216500130
|View full text |Cite
|
Sign up to set email alerts
|

How Do Homeowners Choose Between Fixed and Adjustable Rate Mortgages?

Abstract: Housing is the most important asset in the portfolio of most households. Understanding the households’ decision on housing finance has important implications from a policy perspective, due to the effects it may have on the housing prices, on the housing market stability and on household welfare. The theoretical literature on housing finance focused on figuring out the optimal choice between fixed rate mortgages (FRMs) and adjustable rate mortgages (ARMs). We argue that the standard economic criteria are someti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This results from the application of the representativeness heuristic, explicated as "restricting internationalization to English-speaking markets," driven by the simplicity in entering contexts featuring a similar culture. Although in different contexts, Jones (2015) and Mugerman et al (2016) similarly find that availability and representativeness interact, with the former affecting the latter. For example, Mugerman et al (2016) discover that decision makers facing long-term investments are influenced first by the short-term interest rate changes available, that later can be representative of fixed or adjustable rate decisions.…”
Section: Availability and Representativenessmentioning
confidence: 99%
See 2 more Smart Citations
“…This results from the application of the representativeness heuristic, explicated as "restricting internationalization to English-speaking markets," driven by the simplicity in entering contexts featuring a similar culture. Although in different contexts, Jones (2015) and Mugerman et al (2016) similarly find that availability and representativeness interact, with the former affecting the latter. For example, Mugerman et al (2016) discover that decision makers facing long-term investments are influenced first by the short-term interest rate changes available, that later can be representative of fixed or adjustable rate decisions.…”
Section: Availability and Representativenessmentioning
confidence: 99%
“…Although in different contexts, Jones (2015) and Mugerman et al (2016) similarly find that availability and representativeness interact, with the former affecting the latter. For example, Mugerman et al (2016) discover that decision makers facing long-term investments are influenced first by the short-term interest rate changes available, that later can be representative of fixed or adjustable rate decisions.…”
Section: Availability and Representativenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Berlinger [ 12 ] argued that the calculation method of APRC misleads the borrowers and strengthens their myopic view. Several authors found that personal traits and psychological effects also play a role in borrowers’ choice [ 13 15 ], while Albertazzi et al [ 16 ] and Gathergood and Weber [ 17 ] emphasized the effects of education and financial literacy. The product characteristics are more complicated in the case of ARMs as compared to FRMs since installments are not a linear function of interest rates [ 18 ].…”
Section: Introductionmentioning
confidence: 99%